European social policy: progressive regression - Streeck, Wolfgang (Köln, 2018)
"European social policy changed with the evolution of European and global capitalism, the scope and shape of European-level international institutions, the size and heterogeneity of "Europe" as a polity, and the politics of the European national welfare state. The paper outlines the long-term trajectory of European social policy, from the intended absorption of national welfare states into one united, federal welfare state to a selective updating of national social policies by European social policies; to multi-level coordination of national systems by special European institutions; to European soft law helping national "modernization" on the "Third Way"; to exposure of national systems to international economic competition as an incentive for "structural reform"; and to subordination of social policy, national and European, to the defense of a common hard currency through fiscal consolidation – from, in other words, federal social democracy to competitive "adjustment" of national social protection and social life to global markets. "